2020 Membership Profile of the Financial Therapy Association - Kristy L Archuleta; Malika Dhakhwa (Journal of Financial Therapy, 2021)
The Financial Therapy Association (FTA) periodically releases a report of the state of its membership. This report is from membership data collected in 2020 as a follow-up to the 2011 and 2013 reports. Since the 2013 report, FTA developed a code of ethics and professional certification. The current report highlights differences in membership characteristics and perspectives of financial therapy and the developing field and profession.
Keywords: financial therapy; Financial Therapy Association